Identifying the Effect of Celastrol Against Ovarian Cancer With Network Pharmacology and In Vitro Experiments - Wang, Xuan; Liu, Qiong; Wu, Sisi; Xu, Nana; Li, Hua; Feng, Aihua (Frontiers in Pharmacology, 2022)
Aim: We aim to reveal the function of celastrol in the treatment of ovarian cancer with network pharmacology and molecular docking. Background: Ovarian cancer is a type of cancer begins in ovaries. Celastrol is a useful bioactive compound derived from the root of Thunder god vine. Method: Celastrol and ovarian cancer targets were determined by datasets. PPI networks were obtained with network pharmacology. Then, GO and KEGG analysis were performed. Molecular docking including CB-Dock and Discovery Studio were conducted. MTT assay was used to evaluate the cell proliferation. Cell apoptosis analysis was measured with fluorescence. RT-PCR and western blot were used to evaluate the expression of core targets. Result: Celastrol had 29 potential targets, while ovarian cancer had 473 potential targets. The core PPI network had 163 nodes and 4483 edges. Biological process of GO analysis indicated the results were related with cellular response to DNA damage stimulus, DNA recombination, cell proliferation, etc. KEGG analysis indicated the pathways were related with cell cycle, viral carcinogenesis, MAPK signaling pathway, etc. The 3 core targets between core PPI network and celastrol targets were MYC, CDC37, and FN1. Celastrol could directly interact with these targets CB-Dock and Discovery Studio. Celastrol inhibited ovarian cancer cell proliferation and prompted ovarian cancer cell apoptosis in a dose manner. RT-PCR and western blot analysis showed celastrol inhibited core targets expression. In addition, celastrol also inhibited the related inflammatory signaling pathways in ovarian cancer cells. Conclusion: Celastrol exerts effective anti-tumor effects in ovarian cancer. Celastrol could regulate cell proliferation, DNA repair and replication, apoptotic process, and inflammatory response in ovarian cancer cells.